The Archaeology and History of Rock-cut Cisterns and Open Water Reservoirs in the Negev Highlands - Junge, Andrea (Bulletin of ASOR, 2023)
This article provides the final assessment of a large-scale optically stimulated luminescence (OSL) dating project of water installations in the arid Negev Highlands, southern Israel. Results from five open reservoirs and five rock-cut cisterns are reported. By sampling spoil piles, feeding channels, and accumulation of sediments within reservoirs and cisterns, their construction and phases of maintenance and abandonment are dated. Conventional wisdom argued for progress from simpler open reservoirs in the Bronze or Iron Ages to the more sophisticated rock-cut cisterns of the Nabatean-Byzantine periods. It is shown that open reservoirs were dug throughout the history of the region, likely from the Early or Intermediate Bronze Ages until the medieval period, including periods with no stone-built remains in the region. The construction of subterranean cisterns, which calls for more resources and skill, characterize the Late Roman/Byzantine to Early Islamic period. The significance of these results for reconstructing the history of human activity in the region is also discussed.